Scrapie in Eastern Libya: Case Report in Sheep - Abdalla, Fawzia F.; Sharif, Monier A. (Al-Mukhtar Journal of Sciences, 2022)
Here we report neuropathological features of scrapie cases detected between 2018 and 2022. Fourteen cases of sheep older than 2 years from several areas in Libya with neurological clinical signs resembling those with Scrapie were submitted to the Veterinary Teaching Hospital at Omar Al-Mukhtar University / Al-Beida. Postmortem examinations were performed on all animals after euthanasia. Samples from different organs were submitted for histopathological examination. Routine Hematoxylin and Eosin stain (HE) was used. Nine cases showed neuronal vacuolation that is characteristic of Scrapie in sheep. Two cases were suspected for Scrapie and need more advanced methods such as Immunohistochemistry (IHC) to confirm the diagnosis. The other three cases were diagnosed with Rabies, Listeria, and Echinococcus granulosus.